2019
DOI: 10.1128/aac.01277-19
|View full text |Cite
|
Sign up to set email alerts
|

Roles of Lytic Transglycosylases in Biofilm Formation and β-Lactam Resistance in Methicillin-Resistant Staphylococcus aureus

Abstract: Staphylococcus aureus is responsible for numerous community outbreaks and is one of the most frequent causes of nosocomial infections with significant morbidity and mortality. While the function of lytic transglycosylases (LTs) in relation to cell division, biofilm formation, and antibiotic resistance has been determined for several bacteria, their role in S. aureus remains largely unknown. The only known LTs in S. aureus are immunodominant staphylococcal antigen A (IsaA) and Staphylococcus epidermidis D prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 54 publications
0
12
0
Order By: Relevance
“…NaHCO 3 (with or without OXA co-exposure) repressed the expression of two key autolysins, atl and sceD; in addition, the expressions of several other key genes involved in cell wall synthesis were repressed by NaHCO 3 -OXA co-exposures (isaA, fmtA, ddh, pbp2) (Table 2). These latter six genes encompass those involved in the formation of nascent (new) peptidoglycan and cell wall restructuring (pbp2, ddh, fmtA) [41][42][43][44], as well as peptidoglycan hydrolases, involved in cell wall turnover and division (atl, sceD, isaA) [45][46][47]. Previous studies have demonstrated that the deletion or inactivation of isaA and fmtA results in increased susceptibility to βlactams, an event independent of impacts on the expression of PBP2a [45,48].…”
Section: Number Of Genes/transcriptionalmentioning
confidence: 99%
See 1 more Smart Citation
“…NaHCO 3 (with or without OXA co-exposure) repressed the expression of two key autolysins, atl and sceD; in addition, the expressions of several other key genes involved in cell wall synthesis were repressed by NaHCO 3 -OXA co-exposures (isaA, fmtA, ddh, pbp2) (Table 2). These latter six genes encompass those involved in the formation of nascent (new) peptidoglycan and cell wall restructuring (pbp2, ddh, fmtA) [41][42][43][44], as well as peptidoglycan hydrolases, involved in cell wall turnover and division (atl, sceD, isaA) [45][46][47]. Previous studies have demonstrated that the deletion or inactivation of isaA and fmtA results in increased susceptibility to βlactams, an event independent of impacts on the expression of PBP2a [45,48].…”
Section: Number Of Genes/transcriptionalmentioning
confidence: 99%
“…These latter six genes encompass those involved in the formation of nascent (new) peptidoglycan and cell wall restructuring (pbp2, ddh, fmtA) [41][42][43][44], as well as peptidoglycan hydrolases, involved in cell wall turnover and division (atl, sceD, isaA) [45][46][47]. Previous studies have demonstrated that the deletion or inactivation of isaA and fmtA results in increased susceptibility to βlactams, an event independent of impacts on the expression of PBP2a [45,48]. Furthermore, the regulation of sceD and isaA transcription is linked, since deletion in isaA results in enhanced expression of sceD [45,46].…”
Section: Number Of Genes/transcriptionalmentioning
confidence: 99%
“…In S. epidermidis and S. aureus, Atl is important for initial adhesion and biofilm formation [53], and has in S. epidermidis been demonstrated to mediate adhesion to vitronectin [54]. In S. aureus IsaA is involved in biofilm formation and isaA mutants form significantly less biofilm [55]. In this study we identified IsaA when S. haemolyticus was grown in the presence of serum.…”
Section: Adhesion To Human Keratinocytes and Bacterial Surface Proteimentioning
confidence: 77%
“…Besides the common factors participating in the control of both genes expression, sceD is positively regulated by sigma B, and by two-component regulatory systems LytSR and SaeRS [30]. While the inactivation of isaA leads to the elevated level of sceD expression, the reciprocal effect was not observed, indicating the overlapping as well as distinct physiological roles of IsaA and SceD [18,21].…”
Section: Introductionmentioning
confidence: 99%
“…They both contribute to cell wall remodeling, are required for normal growth of S. aureus and are associated with S. aureus virulence [18,19,20]. Each of them contributes differently to biofilm formation and beta-lactam resistance, and they have opposite effects on S. aureus cells clumping and septation [18,21,22,23,24].…”
Section: Introductionmentioning
confidence: 99%